Pengaruh Metode Pembelajaran Small Group Discussion terhadap Critical Thinking Siswa - Eko Budi Utomo; Taufiq Hidayat (IKIP PGRI Bojonegoro, 2023)
Abstract: Responding to 21st century education, learning is oriented towards learning 21st century skills. 21st century learning uses a term known as 4Cs (critical thinking, communication, collaboration, and creativity). These skills are very important and necessary for 21st century education. This study aims to determine whether there is an effect of the Small Group Discussion learning method on students' critical thinking abilities. This research method is quantitative research and the type of research used is quasi-experimental. The research design used was posttest only control design. The population is all of class X with cluster random sampling where class X D is the control class and class X C is the experimental class. The results of data analysis obtained an average value of 86.42 for the experimental class and for the control class with an average value of 78.47, so it is proven that the Small Group Discussion method is better than the lecture method. As well as the obtained t value 17.226 > t table 2.001 and when viewed from a significance value of 0.000 <0.05 then Ho is rejected. So that the results of this study concluded that there was an influence of the Small Group Discussion learning method on the critical thinking of class X students in economics lessons at MAN 2 Bojonegoro in the 2022/2023 academic year. Abstrak: Merespon pendidikan abad 21 maka pembelajaran diorientasikan menjadi pembelajaran keterampilan abad 21. Pembelajaran abad 21 menggunakan istilah yang dikenal sebagai 4Cs (critical thinking, communication, collaboration, and creativity). Keterampilan-keterampilan tersebut sangat penting dan diperlukan untuk pendidikan abad ke-21. Penelitian ini bertujuan untuk mengetahui apakah ada pengaruh metode pembelajaran Small Group Discussion terhadap kemampuan critical thinking siswa. Metode penelitian ini adalah penelitian kuantitatif dan jenis penelitian yang digunakan adalah kuasi eksperimen. Desain penelitian yang digunakan posttest only control design. Populasinya seluruh kelas X dengan pengambilan sampel secara cluster random sampling dimana kelas X D sebagai kelas kontrol dan kelas X C sebagai kelas eksperimen. Hasil analisis data diperoleh nilai rata- rata kelas eksperimen 86,42 dan kelas kontrol dengan nilai rata- rata 78,47, sehingga terbukti bahwa metode Small Group Discussion lebih baik dibandingkan metode ceramah. Serta diperoleh nilai t hitung 17,226 > t tabel 2,001 dan bila dilihat dari nilai signifikansi 0,000 < 0,05 maka Ho ditolak. Sehingga hasil penelitian ini disimpulkan ada pengaruh metode pembelajaran Small Group Discussion terhadap critical thinking siswa kelas X pada pelajaran ekonomi di MAN 2 Bojonegoro tahun ajaran 2022/2023.